Communication Strategy Of Counseling For Vegetable Farming Group In Waiheru Village, Ambon Baguala Teluk District - Jorgen Tuasuun; Paul Melkianus Puttileihalat; Risyart. A. Far Far (International Journal of Economics, Business and Innovation Research, 2023)
The purpose of this research is to Know communication strategy for Vegetable Farmer Groups in Waiheru Village, Teluk Ambon Baguala District and to find out changes in the behavior of Vegetable Farmer Groups in Waiheru Village, Teluk Ambon Baguala District as an effect of the agricultural extension communication strategy. This research was conducted from November 2022 to December 2022. The type of research used is descriptive qualitative. The population in this study were 10 vegetable farmer groups in Waiheru village with a sample of 20 people. The data collected includes primary data and secondary data with the data analysis technique used is descriptive qualitative analysis. The results of the research show that the Counseling Communication Strategy and behavior change are in the adequate category. And based on the results of observations, interviews and documentation, it shows that there is a change in behavior as an effect of the implemented counseling communication strategy.